Estimation of Depth to Magnetic Sources Using Gradient Inversion Method: A Case of Aeromagnetic Field of Binji, North-Western Nigeria - Nwankwo, L.I.; Akinmadeyan, O.C.; Lawal, T.O.; Ige, S.O.; Saleh, A. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2016)
The depth to magnetic sources has been estimated from gradient inversion analysis of the acquired aeromagnetic magneticdata of Binji, north-western Nigeria. The study area is bounded by Longitude 4° 30’ E and 5° E and Latitude 13° N and 13°30’ N. The total magnetic field was separated into regional and residual fields using least squares polynomial fit, whiletwenty two (22) profiles of the residual magnetic fields were subsequently used to determine depth to magnetic sources.The depths vary from 0.22 km to 2.19 km with an average of 1.26 km. Since estimation of depth to magnetic sources is alsoregarded as a proxy for sedimentary thickness; the results showed that the sedimentary layer is not thick enough forhydrocarbon prospect and therefore confirm that petroleum exploration may not be plausible in the study area.